General principles of law and international investment arbitration - Gattini, Andrea; Tanzi, Attila; Fontanelli, Filippo (Nijhoff international investment law series, 2018)
In General Principles of Law in Investment Arbitration, the authors address selected general principles of law, assessing their functions in investment arbitration. The resulting picture is that of a lively source that escapes doctrinal straitjackets and maintains its relevance.--